Vol. 743 : High Technology: Research and Applications (HTRA 2016) The V International Science and Engineering Conference, Decembe 5-7, 2016, Tomsk, Russia [proceedings] - Osokin G. E. Georgy Evgenievich; Kulinich E. A. Ekaterina Aleksandrovna (2017, 2017)
Title screen